Effect of shielded metal arc welding on microstructure, hardness, and tensile strength of nodular cast iron - Agung Setyo Darmawan, Agung Setyo Darmawan; Agus Dwi Anggono, Agus Dwi Anggono; Agus Yulianto, Agus Yulianto; Bambang Waluyo Febriantoko, Bambang Waluyo Febriantoko; Masyrukan, Masyrukan; Turnad Lenggo Ginta, Turnad Lenggo Ginta; Abdul Hamid, Abdul Hamid (2023)
Welding plays an important role in the component joining process. This study aimed to determine the effect of shielded metal arc welding on the microstructure, hardness, and tensile strength of nodular cast iron. Shielded metal arc welding was performed using AWS A5.15 Eni-CL electrodes. Scanning Electron Microscope is used for metallographic observation. Hardness testing was carried out on base metal, heat-affected zone, and weld metal. This hardness test uses the Vickers technique. Tensile testing was carried out to determine the effect of welding on tensile strength. The results of the metallographic investigation showed the disappearance of the ferrite phase and the appearance of the ledeburite phase in the heat-affected zone and weld metal. The area with the highest hardness occurs in the heat-affected zone while the lowest hardness occurs in the weld metal. There is a decrease in the tensile strength of nodular cast iron due to the welding process